Influence of nano AL2O3 on compression ignition engine characteristics fuelled with Mahua biodiesel. (2023) - Backiyaraj, A.; Parthasarathy, M.; Murugu Nachippan, N.; Senthilkumar, P.B.; Kumaran, T.
Abstract: Growing energy demand and rising emissions have prompted testing on alternative energy sources for IC engine applications. Alternative energies are commonly extracted from biomass waste, algae and plant seeds. Many environmental difficulties develop as a result of the use of petroleum products in IC engines. As a result, adapting an alternative fuel to an existing engine may necessitate some design changes in order to achieve greater or nearly equal performance of conventional fuels. The primary objective of this experiment is to increase the efficiency of the engine and reduce the concentration of HC, CO2 and NOx. The experimental investigation was assessed in a single cylinder, compression ignition engine fuelled with mahua biodiesel and its diesel blends with AL2 O3 nano additive. The engine was analysed with different test fuels such as Diesel, 10 % mahua biodiesel + 90 % diesel (B10), 20 % mahua biodiesel + 80 % diesel (B20), 70 % diesel (B30) at different load conditions. From the tested fuel, 20 % mahua biodiesel + 80 % diesel (B20) showed reasonable performance and tail pipe emission compared to other biodiesel blends. The preparation of nano blended biodiesel was based on 80 % of Diesel, 20 % of mahua biodiesel and 10, 25, 50 ppm of nano AL2 O3. The 50 ppm of nano AL2 O3 blended biodiesel shows better thermal efficiency and reduced emissions due to presence of nanoparticle in the blends which enhance the fuel atomization characteristics. BTE of 50 ppm of nano AL2 O3 blended biodiesel increased 6.05 %, when compared with the diesel. The emission of HC, CO, NOx, and Smoke by 50 ppm of nano AL2 O3 blended biodiesel was reduced by 19.52 %, 29.81 %, 14.48 %, and 23.35 %, respectively when correlated to base fuel. On whole, it was concluded that nano AL2 O3 blended mahua biodiesel found to be a better alternative energy for unmodified existing CI engine.